MULTIKULTURALISME DI PURA BESAKIH KARANGASEM - A.A. Gde Bagus (Forum Arkeologi, 2012)
Study of “Multiculturalism in Pura Besakih, Karangasem” was performed to determine the form and values of Balinese culture in multiculturalism. This research used the theory of religious, Koentjaraningrat’s functional theory and Ida Bagus Triguna’s symbolic theory. The data were collected through observation, interviews, and library research. The data were analyzed qualitatively and supported by quantitative analysis. The results showed that the shape of multiculturalism in Pura Besakih is shown by the existance of palinggih in the forth mandala. Multiculturalism had been there since the Bali Kuna evidenced by the remains of Lingga, Shiva - Buddha statue placed in a palinggih. At the era of King Watu Renggong in the 14th century AD, it was developed further by establishing Palinggih Ratu Syahbandar, using Balinese architecture, dominated by red color and celebrated on the day of Galungan. The worship was conducted by the Balinese and ethnic of Tionghoa who were usually traders. Ratu SyahBandar was believed to be the god of commerce which is considered to give a blessing. The existence of Buddha and Shiva statue and Palinggih Ratu Syahbandar as a form of a very wise policy of the founders of Pura Besakih highly appreciated differences in beliefs. The values of Balinese local genius which contained in multiculturalism, i.e Rwa Bhineda, Tatwamasi, Tri Kaya Parisudha, and Tri Hita Karana. These cultural values had driven the Balinese and other community to be well integrated. In addition, there are some cultural samenesses between Hindu and Buddha. Kajian “Multikulturalisme di Pura Besakih Karangasem”, dilakukan untuk mengetahui bentuk dan nilai-nilai budaya Bali dalam multikulturalisme. Dalam penelitian ini teori yang digunakan adalah teori religi dan fungsional dari Koentjaraningrat, dan teori simbol dari Ida Bagus Triguna. Pengumpulan data dilakukan dengan metode observasi, wawancara, studi kepustakaan, dan analisis data dilakukan dengan kualitatif ditunjang dengan analisis kuantitatif. Hasil penelitian menunjukkan bahwa bentuk multiklturalisme di Pura Besakih, adanya palinggih pada mandala IV. Multikulturalisme tersebut sudah ada sejak jaman Bali Kuna dibuktikan adanya tinggalan Lingga, arca Siwa – Budha yang ditempatkan dalam satu palinggih. Jaman Watu Renggong abad XIV M dikembangkan lagi dengan mendirikan Palinggih Ratu Syahbandar, memakai arsitektur Bali dengan memakai warna merah, Perayaannya pada hari raya Galungan. Pemujaan dilakukan oleh masyarakat Bali dan etnis Tionghoa yang mempunyai profesi berdagang. Ratu Syah Bandar dipercaya sebagai dewa perdagangan yang dianggap dapat memberikan berkah. Adanya Palinggih arca Siwa Buddha dan Ratu Syahbandar ini sebagai wujud kebijakan yang amat arif dari pendiri Pura Besakih yang sangat menghargai perbedaan keyakinan. Nilai-nilai kearifan lokal budaya Bali yang terkandung dalam multikulturalisme tersebut, yaitu Rwa Bhineda, Tatwamasi, Tri Kaya Parisudha, Tri Hita Karana. Nilai budaya inilah yang telah mendorong orang Bali dan komonitas lainnya dapat berintegrasi dengan baik. Selain nilai-nilai budaya tersebut ada faktor lain yaitu adanya persamaan kultural antara Hindu dan Buddha.